Medium-chain Acyl-CoA dehydrogenase deficiency: evaluation of genotype-phenotype correlation in patients detected by newborn screening - Gramer, Gwendolyn; Haege, Gisela; Fang-Hoffmann, Junmin; Hoffmann, Georg F.; Bartram, Claus R.; Hinderhofer, Katrin; Burgard, Peter; Lindner, Martin (JIMD reports, 2015)
Background: Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is included in many newborn screening programmes worldwide. In addition to the prevalent mutation c.985A>G in the ACADM gene, potentially mild mutations like c.199T>C are frequently found in screening cohorts. There is ongoing discussion whether this mutation is associated with a clinical phenotype. Methods: In 37 MCADD patients detected by newborn screening, biochemical phenotype (octanoylcarnitine (C8), ratios of C8 to acetylcarnitine (C2), decanoylcarnitine (C10) and dodecanoylcarnitine (C12) at screening and confirmation) and clinical phenotype (inpatient emergency treatment, metabolic decompensations, clinical assessments, psychometric tests) were assessed in relation to genotype. Results: 16 patients were homozygous for c.985A>G (group 1), 11 compound heterozygous for c.199T>C and c.985A>G/another mutation (group 2) and 7 compound heterozygous for c.985A>G and mutations other than c.199T>C (group 3) and 3 carried neither c.985A>G nor c.199T>C but other known homozygous mutations (group 4). At screening C8/C2 and C8/C10, at confirmation C8/C2, C8/C10 and C8/C12 differed significantly between patients compound heterozygous for c.199T>C (group 2) and other genotypes. C8, C10 and C8/C2 at screening were strongly associated with time of sampling in groups 1 + 3 + 4, but not in group 2. Clinical phenotype did not differ between genotypes. Two patients compound heterozygous for c.199T>C and a severe mutation showed neonatal decompensation with hypoglycaemia. Conclusion: Biochemical phenotype differs between MCADD patients compound heterozygous for c.199T>C with a severe mutation and other genotypes. In patients detected by newborn screening, clinical phenotype does not differ between genotypes following uniform treatment recommendations. Neonatal decompensation can also occur in patients with the presumably mild mutation c.199T>C prior to diagnosis.